Do Banks Monitor Corporate Decisions? Evidence from Bank Financing of Mergers & Acquisitions - HUANG, Sheng (Institutional Knowledge at Singapore Management University, 2012)
We examine whether banks, in providing nancing for the deals, monitor rms mergers and acquisitions to the extent that will bene t acquirers shareholders. Incon- sistent with the conventional theoretical argument, we do not nd that bank- nanced deals are associated with better stock or accounting performance than bond- nanced deals or deals paid with internal cash. There is strong evidence instead that banks tighten up the loan contract terms in nancing the deals, such as cutting short the loan maturity and imposing higher collateral requirement and more covenant restrictions. However, bank- nanced deals are more likely to be terminated when they experience more negative stock market reactions to deal announcements, suggesting that banks may be subject to the pressure of shareholder dissent. Overall, our results suggest that banks do not monitor to enhance rm value but rather protect themselves from downside risks through more stringent loan contract terms. This study highlights the passive role of banks in corporate decisions outside of credit default states and covenant violations.